Enhancing Pancasila Student Profiles: Android-Based Learning Media in the Independent Curriculum for Elementary Schools - Hadi Purwanto; Yessy Yanita Sari; Somariah Fitriani (STAI Hubbulwathan Duri, 2024)
This study focuses on the development and evaluation of Android-based learning media designed to integrate the Pancasila Student Profile into the Independent Curriculum for elementary schools. The media aims to enhance character education and support digital-era learning. A research and development (RD) approach was employed, utilizing the Four-D model, encompassing Define, Design, Develop, and Disseminate stages. Validation was conducted by media and content experts, followed by trials with fourth-grade students. Data collection included expert assessments, student feedback, and comparative analysis of learning outcomes in experimental and control classes. Validation by media experts yielded an average score of 4.7, and content experts gave an average score of 4.47, both classified as